2018
DOI: 10.37761/rsqp.v84i2.143
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMIZACIÓN DEL RENDIMIENTO DE LA EXTRACCIÓN DE ACEITE DE SEMILLAS DE Vitis vinifera CON CO2 SUPERCRÍTICO

Abstract: Se optimizó el rendimiento de la extracción de aceite de la semilla de uva, variedad Quebranta, con el método superficie respuesta (MSR), se consideraron tres factores: presión (Pbar), temperatura (T) y flujo de CO2 (F), las variables respuesta fueron el rendimiento de aceite, el valor peróxido (POV) y anisidina. Se caracterizó la semilla y estableció el tamaño de partícula de la semilla para la extracción de aceite. Se realizaron las extracciones según el diseño MSR y se calcularon los rendimientos de aceite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…As mentioned by Roshanpour et al [33], the peroxide value does not determine by itself the oxidation stability of oils such as grape seed oil. Therefore, the anisidine index was used to investigate a secondary oxidation, whose value was 2.70 ± 0.05 in this study and was close to the values found by Barriga-Sánchez et al [13] in Quebranta (Vitis vinifera) grape seed oil extracted with supercritical CO2 and hexane: 2.30 ± 0.20 and 3.06 ± 0.15, respectively. This index was less than the quality limit required for fish oil (≤ 20).…”
Section: Chemical Qualities Of Grape Seed Oilsupporting
confidence: 87%
See 3 more Smart Citations
“…As mentioned by Roshanpour et al [33], the peroxide value does not determine by itself the oxidation stability of oils such as grape seed oil. Therefore, the anisidine index was used to investigate a secondary oxidation, whose value was 2.70 ± 0.05 in this study and was close to the values found by Barriga-Sánchez et al [13] in Quebranta (Vitis vinifera) grape seed oil extracted with supercritical CO2 and hexane: 2.30 ± 0.20 and 3.06 ± 0.15, respectively. This index was less than the quality limit required for fish oil (≤ 20).…”
Section: Chemical Qualities Of Grape Seed Oilsupporting
confidence: 87%
“…Yousefi et al [34] evaluated seed oil from two Shahrodi grape varieties (Lal and Khalili), extracted by the Soxhlet method with petroleum ether as solvent, obtaining POV values of 9.30 and 10.63 milliequivalent/kg respectively. Barriga-Sánchez et al [13] found a POV of 38.44 ± 0.44 milliequivalent/kg for Quebranta grape seed oil (Vitis vinifera) extracted with hexane. Our lower POV number indicates a good quality of oil and a good preservation status, possibly due to the supercritical CO2 oil extraction technique used.…”
Section: Chemical Qualities Of Grape Seed Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the highest POV (Table 4) was determined for QGSO from Ica and Chincha, 1.91 ± 0.18 and 1.54 ± 0.14 milliequivalents of peroxide/kg oil, respectively, although no significant differences were found between the BBGSO and QGSO from Chincha. Barriga-Sánchez et al (2018) found a POV of 38.44 ± 0.44 milliequivalent/kg for Quebranta grape seed oil (Vitis vinifera) extracted with hexane. Our lower number of POV indicates a good quality of oil and a good preservation status, possibly due to the supercritical CO 2 oil extraction technique used.…”
Section: Povmentioning
confidence: 99%